OsB9−: An Aromatic Osmium-Centered Monocyclic Boron Ring - Yu, Rui; Pan, Sudip; Cui, Zhong-hua (Frontiers in Chemistry, 2021)
Transition-metal-centered monocyclic boron wheels are important candidates in the family of planar hypercoordinate species that show intriguing structure, stability and bonding situation. Through the detailed potential energy surface explorations of MB9- (M = Fe, Ru, Os) clusters, we introduce herein OsB9- to be a new member in the transition-metal-centered borometallic molecular wheel gallery. Previously, FeB9- and RuB9- clusters were detected by photoelectron spectroscopy and the structures were reported to have singlet D9h symmetry. Our present results show that the global minimum for FeB9- has a molecular wheel-like structure in triplet spin state with Cs symmetry, whereas its heavier homologues are singlet molecular wheels with D9h symmetry. Chemical bonding analyses show that RuB9- and OsB9- display a similar type of electronic structure, where the dual sigma + pi aromaticity, originated from three delocalized sigma bonds and three delocalized pi bonds, accounts for highly stable borometallic molecular wheels.